Gamification as support to reading learning: motivation and engagement of students with dyslexia from Brazilian schools - Campos, Jailma do Socorro Uchôa Bulhões (2020)
As a lifelong Specific Learning Difficulty, dyslexia may continue in adolescence and adulthood. Adolescent students with dyslexia still experience difficulties with reading accuracy and comprehension, and a lower motivation in learning. Nonetheless, dyslexia can be manageable with appropriate educational intervention. The Brazilian educational context needs further discussion with the schools to create proper pedagogic strategies focused on giving learners more challenges and opportunities to keep developing their reading skills. This thesis aims to understand how gamification – a process of integrating game features into a non-game context with the aim to increase motivation, participation, enjoyment, and engagement – can be used as pedagogical support to enhance reading learning by students with dyslexia. This investigation is a qualitative case study inspired in Design Thinking, a human-centered and iterative approach used to create solutions to solve problems, which led to the iterative prototyping of a gamified storytelling. The research was developed in an immersive process involving seven participants (three adolescent students with dyslexia and four educators from two Brazilian public schools) over four adapted phases: phase 01 – immersion and exploration, in which a participant-observation was conducted in combination with structured interviews aiming to map the students’ dyslexia needs and difficulties and learn about them, and a documentary analysis and open-ended questions in order to investigate and understand the educational context of Multifunctional Resource Rooms; phase 02 – analysis and definition, in which the content analysis technique was used to analyze and cross the data collected in phase 01; phase 03 – ideation, which was developed as a process of design and creation of the gamified plan/tool registered as field notes; and phase 04 –iterative prototyping, to test, obtain participants’ feedback with the purpose of iterating and then redefining the gamified tool. At this stage, instruments such as scales, questionnaires, and interviews with open-ended questions were applied to get the participants’ opinions on the tool. Moreover, all the testing sessions were video-recorded and subsequently transcribed and analyzed. Content analysis was the technique used to code textual material and to make interpretations. Based on the main findings of this study, some conclusions are highlighted. First, mapping and characterizing adolescent students with dyslexia difficulties allowed a deep understanding of the learners’ profiles, their thoughts, feelings, motivation to read/write, expectations about school support, needs, and evinced and self-perceived difficulties. In addition, the investigation of Multifunctional Resource Rooms elucidated the insufficient support provided to students with dyslexia in the Brazilian Special Educational context. Moreover, the process of ideation, design, prototyping, and testing of gamified storytelling beyond the creative and innovative process provided information about the contributions of a tool embedded with game mechanics to obtain a more intrinsic motivation, enjoyment, engagement, and learning/demonstration of reading skills. The participants’ evaluation provided perceived information about the contributions of the gamified experience to motivation, engagement, and learning, in addition to impressions of the paper and digital versions of the tool. This thesis mainly provides a digital prototype as an example of a gamified tool to support the reading activities of learners with reading impairment.